MEMORY AND (TRANS)GENDER: ON HERCULINE BARBIN'S AUTOBIOGRAPHY - Resende, Marcelo Branquinho [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias Humanas & Sociais, 2018)
The following article intends to question, through Judith Butler's theory of performativity, along with Maurice Halbwachs' memory theories, how much collective memory influences the modulation of subjectivity of oneself and the way in which we account ourselves as beings in autobiographical or confessional narratives. For this, we take as object of study Herculine Barbin's autobiography, which is known as one of the first of the genre to be written by a person who is designated as intersex/transgender.
Keywords: memory; autobiography; gender; transexuality